2012
DOI: 10.1016/j.cell.2012.11.026
|View full text |Cite|
|
Sign up to set email alerts
|

β-Catenin-Driven Cancers Require a YAP1 Transcriptional Complex for Survival and Tumorigenesis

Abstract: Summary Wnt/β-catenin signaling plays a key role in the pathogenesis of colon and other cancers; emerging evidence indicates that oncogenic β-catenin regulates several biological processes essential for cancer initiation and progression. To decipher the role of β-catenin in transformation, we classified β-catenin activity in 85 cancer cell lines in which we performed genome scale loss-of-function screens and found that β-catenin active cancers are dependent on a signaling pathway involving the transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
634
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 680 publications
(661 citation statements)
references
References 69 publications
22
634
2
3
Order By: Relevance
“…YAP mutant analysis should eventually test this idea. There is also cross talk between YAP and Wnt signaling on different levels, including beta catenin (34) and Disheveled (64; for a review, see reference 65). In these situations, it is the phosphorylated YAP that is active.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…YAP mutant analysis should eventually test this idea. There is also cross talk between YAP and Wnt signaling on different levels, including beta catenin (34) and Disheveled (64; for a review, see reference 65). In these situations, it is the phosphorylated YAP that is active.…”
Section: Figmentioning
confidence: 99%
“…YAP also has been shown to play a role in myoblast (31) and neuronal stem cell (32,33) differentiation. Additionally, recent evidence suggests that YAP is involved in cell survival in Wnt-and ␤-catenin-dependent colorectal cancers (34). Clearly, YAP and PyST are both pleiotropic in their actions, with considerable overlap in their biology.…”
mentioning
confidence: 99%
“…Wnt signaling stabilizes TAZ and promotes TAZ‐dependent transcriptional activation of genes regulated by the TEA domain/Transcription Enhancer Factor (TEAD) family of transcription factors, the main binding partners of both TAZ and YAP1 (Azzolin et al ., 2012). Moreover, β‐catenin and Yes‐associated protein (YAP) act as coactivators of the T‐BOX 5 (TBX5) nuclear factor (Rosenbluh et al ., 2012). Although recent results of Park et al .…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, the Hahn laboratory reported that in colon cancer, YAP and the transcription factor TBX5 form a complex with b-catenin and phosphorylation of YAP by the YES tyrosine kinase leads to localization of this complex to the promoter of anti-apoptotic genes, including BCL2L1 and BIRC5, defining a b-catenin-YAP-TBX5 complex essential for the transformation and survival of b-catenin-driven colon malignancy. 17 Most recently, using advanced tools of proteomics and proximity ligation, the O'Neill laboratory documented that Ras association domain family 1C (RASSF1C) was able to target Src and Yes kinases to epithelial cell to cell junctions to promote tyrosine phosphorylation of YAP along with b-catenin and E-cadherin and thereby promoting YAP-mediated invasion of carcinomas. 16 All these studies implicate tyrosine phosphorylation in the function of YAP.…”
Section: Introductionmentioning
confidence: 99%